2021
DOI: 10.3389/fphar.2021.664022
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Chemistry, Pharmacokinetics, Pharmacology, Clinical Applications, Adverse Events, and Quality Control of Indigo Naturalis

Abstract: Indigo naturalis (IN), which is derived from indigo plants such as Strobilanthes cusia (Nees) Kuntze, Persicaria tinctoria (Aiton) Spach, and Isatis tinctoria L., has been traditionally used in the treatment of hemoptysis, epistaxis, chest pain, aphtha, and infantile convulsion in China for thousands of years. Clinical trials have shown that the curative effect of IN for psoriasis and ulcerative colitis (UC) is remarkable. A total of sixty-three compounds, including indole alkaloids, terpenoids, organic acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…40 41 Activation of AhR has been suggested as a possible mechanism in the pathobiology of IN-induced PAH. [42][43][44] As a natural product, the composition of IN varies widely among sources, 45 making batch-to-batch consistency difficult to control. To mitigate these risks, a single molecule AhR agonist that achieves the same therapeutic effect as IN could improve quality control.…”
Section: Discussionmentioning
confidence: 99%
“…40 41 Activation of AhR has been suggested as a possible mechanism in the pathobiology of IN-induced PAH. [42][43][44] As a natural product, the composition of IN varies widely among sources, 45 making batch-to-batch consistency difficult to control. To mitigate these risks, a single molecule AhR agonist that achieves the same therapeutic effect as IN could improve quality control.…”
Section: Discussionmentioning
confidence: 99%
“…The plant Indigo naturalis is best known as a source of blue dye, but it also has traditional medicinal uses in China. Its main bioactive components are the bis-indoles indigo and indirubin, which are formed by non-biological reactions during processing ( Sun et al, 2021 ). Therapeutic benefit of Indigo naturalis in ulcerative colitis (UC, a common inflammatory disease of the colon) was proven by recent clinical trials ( Naganuma et al, 2018 ; Naganuma et al, 2020 ; Uchiyama et al, 2020 ).…”
Section: Case Studiesmentioning
confidence: 99%
“…Response rates for the herbal medicine were comparable to the most effective western drugs, including biologics that target TNFα, and patients whose disease was not well-managed by western drugs responded well to the herbal preparation ( Naganuma et al, 2020 ). The active ingredients in Indigo Naturalis , Indigo and indirubin, are almost insoluble in water and have very poor oral bioavailability ( Sun et al, 2021 ). They are thought to act directly in the gut, where their concentration is locally high following ingestion of Indigo naturalis powder.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies have reported that CHD has antipyretic, anti-inflammatory, and detoxifying properties. Recently, it has been demonstrated to have excellent clinical efficacy in treating gastrointestinal diseases and AD [ 19 , 20 , 21 ]. Furthermore, CHD contains indigo and indirubin that are effective in treating various diseases, such as bacterial infections, cancer, and inflammation, by affecting the immune system [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%